Indoor air quality guide : best practices for design, construction, and commissioning. (American Society of Heating, Refrigerating, and Air-Conditioning Engineers, 2009)
"Comprehensive, practical resource on design and construction for enhanced indoor air quality (IAQ) in commercial and institutional buildings. Useful for architects, engineers, building owners concerned with high-quality indoor environment. Focuses on today's major IAQ issues: moisture management, ventilation, filtration and air cleaning, and source control"--Provided by publisher.
Keywords: Commercial buildings.; Public buildings.; Buildings -- Environmental engineering.; Indoor air quality.; Indoor air pollution.; Engineering.; elektronické knihy; electronic books